Wealth of nomads – an exploratory analysis of livestock inequality in the Saami reindeer husbandry - Næss, Marius Warg; Bårdsen, Bård-Jørgen (Humanities and Social Sciences Communications, 2023)
The evolution of political complexity is a perennial issue in humanities and social sciences. While social inequality is pervasive in contemporary human societies, there is a view that livestock, as the primary source of wealth, limits the development of inequalities, making pastoralism unable to support complex or hierarchical organisations. Thus, complex nomadic pastoral organisation is predominantly caused by external factors: historically, nomadic political organisations mirrored the neighbouring sedentary population’s sophistication. Using governmental statistics from 2001 to 2018 on reindeer herding in Norway, this study demonstrates that there is nothing apparent in pastoral adaptation with livestock as the main base of wealth that levels wealth inequalities and limits social differentiation. This study found that inequality generally decreased in terms of the Gini coefficient and cumulative wealth. For example, the proportion owned by the wealthy decreased from 2001 to 2018, whereas the proportion owned by the poor increased. Nevertheless, rank differences persisted over time with minor changes. In particular, being poor is stable; around 50% of households ranked as poor in 2001 continued to be so in 2018. In summary, the results of this study indicate that pastoral wealth inequality follows the same pattern as all forms of wealth. Wealth accumulates over time, and while the highest earners can save much of their income (i.e., newborn livestock), low earners cannot. Thus, high-earners can accumulate more wealth over time, leading to considerable wealth inequality. Wealth of nomads – an exploratory analysis of livestock inequality in the Saami reindeer husbandry publishedVersion